Are the Upwardly-Mobile More Left-Wing? - Andrew E. Clark; Maria Cotofan (Institute of Labor Economics (IZA), 2023)
It is well-known that the wealthier are more likely to have Right-leaning political preferences. We here in addition consider the role of the individual's starting position, and in particular their upward social mobility relative to their parents. In 18 waves of UK panel data, both own and parental social status are independently positively associated with Rightleaning voting and political preferences: given their own social status, the upwardly-mobile are therefore more Left-wing. We investigate a number of potential mediators: these results do not reflect the relationship between well-being and own and parents' social status, but are rather linked to the individual's beliefs about how fair society is.
Keywords: A14; C25; D31; D63; J28; J62; 330; social mobility; voting; redistribution; satisfaction; fairness